Hubungan pengetahuan tentang Covid-19 dengan perilaku protokol kesehatan di perkantoran - Imelda Ritunga; Hanna Tabita Hasianna Silitonga; Wira Widjaya Lindarto; Siusanto Hadi; Etha Rambung; I Made Irham Muhammad; Agnes Atmajaya (Holistik Jurnal Kesehatan, 2022)
Background: A possible office Covid cluster could result from office activity during a pandemic. Implementing health protocols is essential to help protect oneself from the transmission of Covid-19 knowledge of Covid-19 decisions to behave according to health protocols.Purpose: To analyze the relationship between knowledge about Covid-19 and the behavior of implementing health protocols in the office environment.Method: Analytical observation was carried out by collecting data cross-sectional. The population consisted of school teachers, samples were taken based on voluntary sampling with online questionnaires, and 114 respondents participated. Questionnaires were made by the research team and tested for validity and reliability. The results of the data were processed statistically with the Spearman correlation test.Results: There is a relationship between knowledge and behavior of health protocols in the office environment: hand washing steps (r=0.255, p=0.006), minimum distance for interaction (r=0.231, p=0.013), and the type of mask used to go to the office (r=0.312, p=0.001).Conclusion: There is a significant relationship between knowledge of Covid-19 and behavior of health protocols in the office environment, so increased knowledge about Covid-19 needs to be continuously pursued to improve health protocol behavior.Keywords: Covid-19; Behavior; Knowledge; RegulationPendahuluan: Kegiatan perkantoran di masa pandemic dapat berpotensi menjadi klaster perkantoran. Perilaku menerapkan protokol kesehatan menjadi hal penting dilakukan untuk membantu memproteksi diri dari penularan COVID-19. Pengetahuan akan Covid-19 menginformasikan keputusan untuk berperilaku sesuai protokol kesehatan.Tujuan: Menganalisis hubungan antara pengetahuan tentang Covid-19 dengan perilaku menerapkan protokol kesehatan di lingkungan kantor. Metode: Dilakukan analitik observational dengan pengambilan data secara cross sectional. Populasi berupa guru-guru sekolah, sampel diambil berdasarkan voluntary sampling dengan kuesioner online, sejumlah 114 responden berpartisipasi. Kuesioner dibuat oleh tim peneliti, dilakukan uji validitas dan reliabilitas. Hasil data diolah statistik dengan uji korelasi Spearman.Hasil:  Terdapat hubungan antara pengetahuan dan  perilaku protokol kesehatan di lingkungan perkantoran, yaitu langkah cuci tangan (r=0.255, p=0.006), jarak minimal berinteraksi (r=0.231, p=0.013), dan jenis masker yang digunakan ke kantor (r=0.312, p=0.001).Simpulan: Terdapat hubungan yang signifikan antara pengetahuan akan Covid-19 dengan perilaku protokol kesehatan di lingkungan perkantoran sehingga peningkatan pengetahuan tentang Covid-19 perlu terus diupayakan agar perilaku protokol kesehatan semakin baik.